Modeling the Dynamic Behavior of Track Transitions Along Shared Track Corridors - Li, Wenjing; Hou, Wenting; Mishra, Debakanta; Tutumluer, Erol (Frontiers in Built Environment, 2021)
This paper presents findings from an analytical modeling effort undertaken to study the dynamic response of track transitions along shared-track corridors. A recently developed train-track-bridge model was used for this purpose. First, the model predictions are verified using field instrumentation data as well as data from other published literatures. Subsequently, the model is used to analyze the dynamic response of a typical bridge approach under the passage of a high-speed passenger train as well as six different freight trains comprising different freight car types. A speed sensitivity analysis of a freight train comprising one specific freight car type is also carried out. Geometric configuration of different freight trains is assessed as well as weight and speed of operation. Different track response parameters, including vertical displacement and rail-tie reaction force, are considered to highlight the differences in the track dynamic behavior under freight and passenger train loading. Analyses in both time and frequency domains illustrate the difference in track behavior under freight and passenger train loading. The significance of gap development at the tie-ballast interface near track transitions has been emphasized by illustrating the effect of tie gap on the dynamic track behavior. The paper concludes by emphasizing the importance of special consideration to track dynamic behavior for shared-track corridors.